AN INTERPRETIVE REVIEW OF ENVIRONMENTAL CONSERVATION IN THE CONTEMPORARY ERA - Sri Ayu Andari Putri Alwaris; Mardan; Muhammad Yusuf (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The role of humans in preserving and managing the environment is very large and covers various aspects of life, including natural resource management, biodiversity protection, application of environmentally friendly technology, and public awareness to protect nature. All these actions are not only important for human survival, but also for the life of all creatures on earth. By integrating the principles of sustainability into everyday life, humans can help keep the earth sustainable for future generations .